2021
DOI: 10.1016/j.amjoto.2020.102796
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between disease severity and serum IL-6 levels in COVID-19 anosmia

Abstract: Background An association between IL-6 levels and cytokine storm syndrome in COVID-19 patients has been suggested. Cases with higher IL-6 levels have more rapid progression and a higher complication rate. On the other hand, COVID-19 cases with anosmia have a milder course of the disease. Objective We aimed to investigate whether there is a relationship between serum IL-6 levels and presence of anosmia in COVID-19 patients. Methods Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
47
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 33 publications
8
47
2
5
Order By: Relevance
“…Nasal obstruction-related loss of smell is very common in viral infections; however, anosmia associated with COVID-19 is not commonly accompanied by nasal obstruction/congestion [6,14,21]. Similarly, in our study, the association of olfactory dysfunction with nasal congestion was found to be low with a ratio of 18.2%.…”
Section: Clinical Features Of Covid-19 Anosmiasupporting
confidence: 58%
See 2 more Smart Citations
“…Nasal obstruction-related loss of smell is very common in viral infections; however, anosmia associated with COVID-19 is not commonly accompanied by nasal obstruction/congestion [6,14,21]. Similarly, in our study, the association of olfactory dysfunction with nasal congestion was found to be low with a ratio of 18.2%.…”
Section: Clinical Features Of Covid-19 Anosmiasupporting
confidence: 58%
“…One plausible mechanism is high viral load in nasal mucosa with secondary inflammation which may result in direct injury to olfactory epithelium [13]. Another plausible mechanism involves angiotensin converting enzyme 2 (ACE2) receptors [14]. The olfactory epithelium has been found to express ACE2 and TMPRSS2, which may enable SARS-CoV-2 to invade the olfactory mucosa and olfactory bulb, and result in subsequent dysfunction [14][15][16].…”
Section: Pathogenesis Of Covid-19 Anosmiamentioning
confidence: 99%
See 1 more Smart Citation
“…The most common symptoms of patients with COVID-19 are fever, cough, shortness of breath, and myalgia/fatigue [1] . Anosmia (loss of smell) and dysgeusia (altered sensation of taste) have been reported in 33–80% of patients with COVID-19 [2] . SARS-CoV-2 is mainly transmitted human-to-human through close contact, respiratory droplets, fomites, and contaminated surfaces [1] .…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID- 19), which started to spread from the wet animal market in the state of Wuhan in China at the end of 2019, was declared as a pandemic by the World Health Organization in March 2020 [1]. This is the third outbreak by coronaviruses in the 21st century.…”
Section: Introductionmentioning
confidence: 99%